1983
DOI: 10.1017/s0022112083002281
|View full text |Cite
|
Sign up to set email alerts
|

Fully developed periodic turbulent pipe flow. Part 1. Main experimental results and comparison with predictions

Abstract: The present paper is the first part of a two-part report on a detailed investigation of periodic turbulent pipe flow. In this investigation, experimental data on instantaneous velocity and wall shear stress were obtained at a mean Reynolds number of 50000 in a fully developed turbulent pipe flow in which the volumetric flow rate was varied sinusoidally with time around the mean. Two oscillation frequencies at significant levels of flow modulation were studied in detail. The higher of these frequencies was of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 3 publications
2
41
0
2
Order By: Relevance
“…Since experimental data in pulsating turbulent flow with large oscillating velocity amplitudes is lacking, experimental results obtained by Tu and Ramaprian [5] are used as the comparison data. Tu and Ramaprian experimentally measured the sectional velocity distribution in the fully developed pulsating turbulent flow of water, in which the Reynolds number was Re = 50,000 and the Womersley number was Wo = 118.5.…”
Section: Verification Of Computer Code For Pulsating Turbulent Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since experimental data in pulsating turbulent flow with large oscillating velocity amplitudes is lacking, experimental results obtained by Tu and Ramaprian [5] are used as the comparison data. Tu and Ramaprian experimentally measured the sectional velocity distribution in the fully developed pulsating turbulent flow of water, in which the Reynolds number was Re = 50,000 and the Womersley number was Wo = 118.5.…”
Section: Verification Of Computer Code For Pulsating Turbulent Flowsmentioning
confidence: 99%
“…Experimental studies on pulsating turbulent flow were conducted actively [1][2][3][4][5][6][7][8][9][10]. All of the measurements were made for fully developed flows with small oscillating velocity amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The Vardy-Brown weighting function has two adjustable parameters, the A and C constants eqs. (18) and (19). Our model already has one parameter over and above the steady state model, namely the constant λ in eq.…”
Section: From Mtm To CMmentioning
confidence: 99%
“…The subject matter of time dependent turbulent pipe flows has considerable interest, both theoretical and practical [17][18][19][20][21]. The basic framework of analysis depends upon the separation of the flow velocity and pressure into a mean component and a turbulent fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…We first review studies of single-phase pulsating pipe flows. Early studies of turbulent pulsating pipe flows were reported by Ramaprian and Tu [9][10][11]. They used a single-component laser-Doppler-anemometry system to measure the local instantaneous velocity in a pipe with an internal diameter of 50 mm and a Reynolds number of 50000.…”
Section: Literature Surveymentioning
confidence: 99%